Annual abstract of statistics 1965 /. - Nigeria. Federal Office of Statistics, Lagos; Nigeria. National Bureau of Statistics (Lagos : National Bureau of Statistics, 1965)
The main objective of the annual abstract is to provide a compendium of the most important statistics for the analysis of socio economic development at the national level. It is useful to officials responsible for policy making and development planning and for those who require reliable data on the changing economy.
oif 19/08/2019
Ref.
Keywords: Economic conditions--Statistics; Industrial statistics; Population--Statistics; Nigeria